The Design, Prototyping, and Formative Evaluation of an Assistive Robotic Table (ART) for Stroke Patients. (April 2017) - Threatt, Anthony L.; Merino, Jessica; Brooks, Johnell O.; Healy, Stan; Truesdail, Constance; Manganelli, Joseph; Walker, Ian; Green, Keith Evan
Objective: This article presents the results of an exploratory study in which 14 healthcare subject matter experts (H-SMEs) in addition to four research and design subject matter experts (RD-SMEs) at a regional rehabilitation hospital engaged in a series of complementary, participatory activities in order to design an assistive robotic table (ART). Background: As designers, human factor experts, and healthcare professionals continue to work to integrate assistive human–robot technologies in healthcare, it is imperative to understand how the technology affects patient care from clinicians' perspectives. Method: Fourteen clinical H-SMEs rated a subset of conceptual ART design ideas; participated in the iterative design process of ART; and evaluated a final cardboard prototype, the rehabilitation hospital's current over-the-bed table (OBT), an ART built with true materials, and two therapy surface prototypes. Four RD-SMEs conducted a heuristic evaluation on the ART built with true materials. Data were analyzed by frequency and content analysis. Results: The results include a design and prototype for the next generation ART and a pneumatically controlled therapy surface, a broadened list of specifications for the future design and implementation of assistive robotic furniture, and final observations. Conclusion: When compared to the rehabilitation hospital's current OBT, the developed ART in this study was successful. Designing novel features is dependent upon ensuring patient safety. The inclusion of clinicians in the participatory iterative design and evaluation process and the use of personas provided a broadened list of specifications for the successful implementation of assistive robotic furniture.